Encyclopedia of Life Sciences 2010
DOI: 10.1002/9780470015902.a0021231
|View full text |Cite
|
Sign up to set email alerts
|

Stable Isotope Ecology

Abstract: Stable isotope geochemistry has proved to be an extremely useful tool in elucidating many ecological problems, with stable isotope ecology comprising the theme of a series of international conferences ( http://www.isoecol.org ). Stable isotopes can be used as biological tracers in the following ways: (i) to identify sources, for instance in determining the identity of basal carbon in a food web; (ii) to distinguish sources, for example to determine whether a breeding animal is using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…); fish, birds, crustaceans, and cephalopods (DeNiro and Epstein , Peterson and Fry , Caut et al . ); and terrestrial mammals and birds), Δ 15 N = 3.22‰ (SD = 0.30) and Δ 13 C = 0.95‰ (SD = 0.53) (henceforth IDF1) ( e.g ., DeNiro and Epstein , Minagawa and Wada , France and Peters , Newton , Caut et al . ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…); fish, birds, crustaceans, and cephalopods (DeNiro and Epstein , Peterson and Fry , Caut et al . ); and terrestrial mammals and birds), Δ 15 N = 3.22‰ (SD = 0.30) and Δ 13 C = 0.95‰ (SD = 0.53) (henceforth IDF1) ( e.g ., DeNiro and Epstein , Minagawa and Wada , France and Peters , Newton , Caut et al . ).…”
Section: Methodsmentioning
confidence: 99%
“…, Hobson , Knoff et al . , Newton ), and may indicate whether individuals are generalist or specialist foragers (Hobson and Sease , Walker and Macko , Knoff et al . ).…”
mentioning
confidence: 99%
“…Recent studies have shown that the isotopic ratios of suction lysimeter waters differ from cryogenically extracted waters (Brooks et al ., ; Figueroa‐Johnson et al ., ; Landon et al ., ; Zhao et al ., ). While there is of course a large literature on isotopes in plant ecophysiology (see review articles of Adams and Grierson, ; Dawson et al ., ; Newton, ), there has been rather little comment on the techniques we use to extract low mobility waters in soils. Physically, we distinguish between water held at suctions less than field capacity (mobile water) and water held at suctions greater than field capacity – usually referred to as plant available water or tightly bound water (Huntington, ).…”
Section: Introductionmentioning
confidence: 97%
“…The analysis of naturally occurring variation in the ratio of isotopes of elements within the tissues of an organism has become a powerful tool for ecologists and has been used to address a range of questions including studying differences in the diet between individuals, sex/age classes, and populations; studying migration patterns and geographic range; and studying life history strategies (Hobson 1999, Hobson E473 and Wassenaar 1999, Newsome et al 2010, Newton 2010. Stable isotope studies comparing the ratios of nitrogen ( 15 N/ 14 N) and carbon ( 13 C/ 12 C) can be particularly informative for comparing differences in diet, trophic position and geographic range (Hobson and Wassenaar 1999, Newsome et al 2010, Newton 2010. This is because of a stepwise enrichment of 15 N with each increase in trophic level, which reflects differences in fractionation between synthesis and excretion.…”
mentioning
confidence: 99%